Sosialisasi Pengelolaan Sampah dan Pelatihan Pembuatan Ecoenzim di SMPN 1 Baitussalam Aceh Besar - Furqan, Muhammad Hafizul; Azis, Daska; Diah, Husna; Gadeng, Ahmad Nubli; Zalmita, Novia; Yulianti, Fitriani; Desfandi, Mirza; Zaki, Ammar; Kamza, Muhjam (LSM Catimore dan Sahabat, 2025)
Problems related to the lack of public understanding about how to process organic waste into something useful and highly useful are problems faced by the general public in environmental conservation. This community service aims to educate waste management and ecoenzyme making training targeting students in schools. and make direct practice on how to process it correctly. Community service is carried out at SMPN 1 Batussalam. Participants in this training activity are all students. The forms of community service activities are socialization, waste management education and ecoenzyme making training. The results of the Ecoenzyme community service are natural liquids resulting from the fermentation of organic waste such as sugar or molasses, fruit or vegetable waste, and water (AC waste, rainwater, tap water) which can be used in many ways and become goods that have high utility value. The manufacturing process takes 3 months with materials from organic waste residue. The equipment needed such as containers, teleman knives and duct tape. Community service suggestions are to provide more intensive socialization to the community about the use of waste so that it has economic value